The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/fsn3.3153
|View full text |Cite
|
Sign up to set email alerts
|

Ginger as an anticolorectal cancer spice: A systematic review of in vitro to clinical evidence

Abstract: Ginger and its derivatives have been shown to be effective in the prevention and treatment of cancer. We undertook a systematic review to answer the question of whether ginger has a role in modifying the biomarkers of cancer in cell culture conditions and on colorectal cancer in randomized clinical trials. We performed a comprehensive search of the literature from Scopus, Embase, Web of Science, PubMed, Cochrane central register of controlled trials, and Cochrane database of systematic reviews. At first, all 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The dose of ginger has not been optimized in most human studies. 7 , 8 Here, we prepared a ginger juice with total phenolics content at 0.8 ± 0.1 mg garlic acid equivalent/mL. The ginger juice selectively inhibited cancer cell growth at a very narrowed dose window.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dose of ginger has not been optimized in most human studies. 7 , 8 Here, we prepared a ginger juice with total phenolics content at 0.8 ± 0.1 mg garlic acid equivalent/mL. The ginger juice selectively inhibited cancer cell growth at a very narrowed dose window.…”
Section: Discussionmentioning
confidence: 99%
“…Ginger roots (Zingiber officinale Roscoe) are common in Asian cuisine. 7 , 8 It is also becoming popular in Western foods, for example, gingerbread (fortification in cookie), ginger tea (fortification in beverage), and ginger powder (fortification as spice). According to the database published by USDA, 100 g fresh ginger roots contain 1.8 g proteins, 17.8 g carbohydrates, 0.7 g lipids, and various minerals and vitamins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In a systematic review of in vitro evidence of ginger as therapy against colon cancer, it was shown to induce apoptosis and resulted in increased levels of several anticancer markers. 40 In an in vitro study, the ginger-derived compound 6-shogaol eliminated breast cancer monolayer cells and spheroid culture. 41 6-Shogaol has also been used on prostate cancer cells where it induced apoptosis through inhibition of signal transducer and activator of transcription 3 (STAT3) and nuclear factor kappa-light-chainenhancer of activated B cells (NF-kB) signaling.…”
Section: Metabolic and Androgenicmentioning
confidence: 99%
“…Evidence exists supporting the use of ginger as prevention and adjunct therapy for various malignancies including colorectal, prostate, pancreatic, and ovarian cancers 39 . In a systematic review of in vitro evidence of ginger as therapy against colon cancer, it was shown to induce apoptosis and resulted in increased levels of several anticancer markers 40 . In an in vitro study, the ginger‐derived compound 6‐shogaol eliminated breast cancer monolayer cells and spheroid culture 41 .…”
Section: Nondermatological Applicationsmentioning
confidence: 99%